Risk Analysis of Escherichia coli Bacteria in Food at Cidu Market, Makassar City - Haerani Haerani; Syamsuddin Syamsuddin; Inayah Inayah (Poltekkes Kemenkes Palu, 2026)
Background: Foodborne diseases remain a major public health concern, particularly in settings where food hygiene and sanitation practices are inadequate. This study aimed to assess the quantitative risk of Escherichia coli contamination in street food sold at Cidu Market, Makassar City, using the Quantitative Microbial Risk Assessment (QMRA) approach. Methods: A cross-sectional study was conducted involving 10 food samples, 10 food handlers, and 100 consumers. Data were collected through direct observation, structured interviews, and laboratory examination of food samples using the Membrane Filter method to determine E. coli contamination levels. Risk characterization was performed following the QMRA framework. Results: All food samples (100%) were contaminated with E. coli, with bacterial counts ranging from 2 to 25 CFU/g. Among consumers, 19% reported health complaints after consuming food from Cidu Market, with abdominal pain as the most frequently reported symptom. QMRA results indicated that the probability of infection per day (Pinf/day), annual probability of infection (Pinf.annual), and probability of illness (Pill) were predominantly classified as high risk. Poor hygiene practices were observed among food handlers, including failure to wash hands with soap (100%), use gloves (100%), wear aprons (90%), wear face masks (80%), and wear head coverings (70%). Conclusion: The findings indicate a high risk of E. coli exposure from street food at Cidu Market. Improving food handler hygiene practices and strengthening routine food safety monitoring are essential to reduce microbial contamination and prevent foodborne diseases.